Entrepreneurial characteristic and commitment in heritage industry in Terengganu / Muhammad Abi Sofian Abdul Halim, Wan Asri Wan Abdul Aziz and Zainuddin Zakaria - Abdul Halim, Muhammad Abi Sofian; Wan Abdul Aziz, Wan Asri; Zakaria, Zainuddin (Research Management Institute (RMI), 2009)
As the creative industry grows from the producing sector into more complexes in industrialization, entrepreneurship will draw more attention to the need for emphasizing on creative industry. There is now a vast of view to measure the entrepreneurial characteristics which are affected to the growth of business commitment. Thus, entrepreneurial characteristics becomes as a variable which have a relationship to the business commitment in creative industry. According to McClelland (1961) and Gartner (1990), several factors in entrepreneurial characteristics are strongly contributed to the performance of small and medium business, such as; need for achievement, locus of control, creativity, innovative and also strategy to grab market opportunities. Bahagian Pembangunan Usahawan, Kraftangan Malaysia has taken responsibility to trained creative entrepreneurs (usahawan kraf) to develop their entrepreneurial characteristic and improving business commitment. Therefore, the purpose of this paper is to measure the relationship between entrepreneurial characteristics toward business commitment among creative entrepreneurs who are registered in Kraftangan Malaysia, Terengganu.